1991/1992 ネン カキ ノ ナンキョク ショウワキチ シュウヘン ノ テイチャク ヒョウカ ニ オケル クロロフィルa ノ エンチョク フラックス - 小達, 恒夫; オダテ, ツネオ; 佐々木, 洋; ササキ, ヒロシ; 福地, 光男; フクチ, ミツオ; Odate, Tsuneo; Sasaki, Hiroshi; Fukuchi, Mitsuo (国立極地研究所, 2004)
P(論文) 1992年1月6日から2月6日の期間,南極昭和基地周辺の定着氷下の水深25あるいは30mにセジメントトラップを設置し,沈降する粒子を補足した.得られた試料を基に,クロロフィルa(Chl a)のフラックスを見積もり,夏季の植物プランクトン大増殖後の現存量低下に対する,沈降による除去の寄与率を評価した.セジメントトラップより上層の積算Chl a濃度は,1月中旬に最大に達した.Chl aフラックスは,Chl a濃度が最大に達した後に高くなった.上層のChl a濃度減少期における,1日当りの減少率は,8.71-10.4mg Chl a m-2 day-1 であった.この時,Chl aフラックスは,上層で起こったChl a減少率の3.6-4.0に過ぎなかった.このことは,植物プランクトンの沈降が,大増殖後にみられる現存量低下の大きな要因ではないことを示す. Sinking particles were collected using sediment traps, which were deployed at depths of 25 or 30m under fast ice near Syowa Station, Antarctica, from January 6 to February 6, 1992. Using the samples, fluxes of chlorophyll a (Chl a) were estimated and the contribution of algal sinking to the decrease of phytoplankton biomass after the summer bloom was evaluated. The Chl a concentration, integrated above the depths at which the sediment traps were deployed, reached a maximum in mid-January. The Chl a flux became high after the maximum of the concentration was recorded. In the Chl a decreasing phase, daily decreasing rates of the Chl a concentrations in the water columns were 8.71-10.4mg Chl a m-2 day-1 . During this period the Chl a fluxes accounted for only 3.6-4.0 of the decreasing rates. These observations imply that algal sinking is not the major process of phytoplankton biomass decrease after the summer bloom. departmental bulletin paper